Multivitamin/Multimineral Supplement Use is Associated with Increased Micronutrient Intakes and Biomarkers and Decreased Prevalence of Inadequacies and Deficiencies in Middle-Aged and Older Adults in the United States. Issue 4 (2nd October 2019) - Wallace, Taylor C.; Frankenfeld, Cara L.; Frei, Balz; Shah, Alpa V.; Yu, Ching-Ray; van Klinken, B. Jan-Willem; Adeleke, Maryann
Abstract: Micronutrient inadequacies are common in older adults and using a multivitamin/multimineral supplement (MVM) may improve their nutritional status. National Health and Nutrition Examination Survey data were analyzed to determine micronutrient intakes based on diet and MVM use in adults aged ≥51 years. Deficiencies were evaluated using nutrient biomarkers. The National Cancer Institute Method was used to estimate usual intakes of 18 micronutrients stratified by age and frequency of MVM use. Compared with food alone, MVM use was associated with higher nutrient intake and lower prevalence of inadequacies of almost all micronutrients examined and improved nutrient biomarker status of folate, iodine, selenium, and vitamins B6, B12, and D. Regular MVM use (≥16 days/month) decreased the odds of clinical deficiency (defined by biomarker status) of vitamins B6 and D but increased the proportion exceeding the tolerable upper intake level of folic acid. Vitamin B6 deficiency in MVM non-users was common and increased with age.